To Arrive Is to Begin: Benjamin Sáenz's Carry Me Like Water and the Pilgrimage of Origin in the Borderlands - Alberto López Pulido (Studies in 20th & 21st Century Literature, 2001)
This essay examines the "pilgrimage of origin" as presented in Benjamin Sáenz's novel Carry Me Like Water. As is the case with other ethnic literature, Carry Me Like Water teaches us that we must first go back before we can move forward and transform our lives. By pilgrimage of origin I make reference to a journey where participants are required to return to the past and the familiar. Unlike the more commonly described linear pilgrimage experience where participants are required to travel beyond the range of their familiar space, the pilgrimage of origin obligates participants to return to their sacred sources of origin and to interpret and experience them in new and transformative ways. Through the character of María Elena developed by Sáenz, Carry Me Like Water represents a "lyric" for explaining and understanding the unique dimensions of Chicana/o experiences in the borderlands.
Keywords: Benjamin Sáenz; pilgrimage of origin; Carry Me Like Water; ethnic literature; journey; past; chicano/a; origin; sacred; transformation; identity; borderlands; border narrative